2008
DOI: 10.1111/j.1600-0625.2008.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting possible zonisamide hypersensitivity syndrome

Abstract: Sulphamethoxazole-HSR but not AC-HSR patients may present a cross-reactivity to ZNS-HSR. The use of LTA to predict a possible ZNS reaction is recommended for SMX-sensitive individuals who prescribed ZNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Neuman et al 77 conducted a study to determine if cross-sensitivity exists among zonisamide, other anticonvulsants, and sulfamethoxazole. Patients included in the study had hypersensitivity reactions after receiving antiepileptic drugs (carbamazepine, phenytoin, or phenobarbital) or sulfamethoxazole.…”
Section: -Hydroxytryptamine Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuman et al 77 conducted a study to determine if cross-sensitivity exists among zonisamide, other anticonvulsants, and sulfamethoxazole. Patients included in the study had hypersensitivity reactions after receiving antiepileptic drugs (carbamazepine, phenytoin, or phenobarbital) or sulfamethoxazole.…”
Section: -Hydroxytryptamine Agonistsmentioning
confidence: 99%
“…77 Ritter et al 77 conducted a retrospective chart review that identified 15 adults and children who had reported a sulfa allergy manifesting as a rash and had been treated with zonisamide. None of the patients had a rash or other type of allergic reaction while taking zonisamide.…”
Section: -Hydroxytryptamine Agonistsmentioning
confidence: 99%
“…9,18,20,21 Skin manifestations include exanthematous rash, blistering eruptions such as erythema multiforme, SJS and TEN. 16,[22][23][24][25] SJS and TEN are severe cutaneous adverse reactions (SCAR). [26][27][28][29][30][31][32][33][34] Epidermal detachment below 10% is defined as SJS, whereas it is considered TEN above 30% [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…DILI may lead to liver failure and transplant. 10,25 Regardless of ethnicity, HSR predisposition can be predicted by the in vitro lymphocyte toxicity assay (LTA). 52,53 The mitochondrial enzyme succinate dehydrogenase-based LTA was validated versus clinical manifestations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation